Compensation Scheme and Financial Well-being of Government Employees in the National Capital Region - Tadeja, Angelica Louise C.; Ranque, Maevel S.; Unico, Maricris; Abante, Marmelo V. (Research Synergy Foundation, 2024)
This research investigates the relationship between compensation and financial well-being among government employees in the National Capital Region (NCR), focusing specifically on the Bureau of Internal Revenue (BIR) Collection Service divisions. Utilizing a descriptive comparative-correlational design, the study analyzes data collected from 129 employees through a structured questionnaire to assess various aspects of the compensation scheme and its impact on financial well-being. The research delves into key elements of the compensation scheme, including salary satisfaction, the bonus structure, job grades, and salary adjustment processes. It evaluates how these factors contribute to employees' overall satisfaction with their compensation. Additionally, the study explores financial well-being by examining indicators such as income sufficiency, debt management, financial knowledge and skills, financial stability, and retirement preparedness. Significant demographic differences in perceptions of compensation and financial well-being are also investigated, with the research analyzing how these perceptions vary across age, gender, job position, years of service, educational attainment, monthly salary, and additional benefits and allowances. One of the central findings of the study is the moderate correlation between compensation and financial well-being, highlighting that improvements in the compensation system can lead to enhanced financial security and satisfaction among employees. While the majority of respondents report moderate satisfaction with their salaries and benefits, concerns remain regarding the adequacy of bonuses, limited opportunities for promotion, and the alignment of salary adjustments with performance. The study also emphasizes the importance of addressing specific demographic concerns, such as providing age-appropriate support, promoting financial literacy across gender identities, and ensuring equitable compensation across different job positions and educational levels. The research concludes with recommendations for policymakers and organizations to reform the compensation scheme, addressing these key areas to improve the financial well-being and satisfaction of government employees in the NCR.